Laboratory diagnosis of Chagas’ heart disease - Ferreira, Antonio Walter; Ávila, Sandra do Lago Moraes de (São Paulo Medical Journal, 1995)
The laboratory diagnosis of Chagas’ disease is a complex one. Factors relating to the host immune response and the antigenic variability of T. cruzi must be considered in the final interpretation of test results. Parasitologic methods for detecting T. cruzi, immunologic methods for detecting T. cruzi antigens in different biological fluids and serologic tests for detection and quantification of different classes of immunoglobulins are well standardized and used in the diagnosis of the acute or chronic phase of the disease. Xenodiagnosis is the most common parasitologic test employed, although it detects only 50% of infections in the chronic phase. Indirect immunofluorescence for detecting IgG and IgM antibodies, hemagglutination and enzyme immunoassay are the serologic tests most frequently employed for diagnosis, to screen blood donors and for seroepidemiologic studies. An important caveat to be remembered is that serologic tests provide only a probable diagnosis, which depends on the prevalence of Chagas disease, as well as on the sensitivity and specificity of the test employed. The use of well defined specific antigens, obtained through recombinant methods or chromatography, opens an important field for the development of very specific tests, without significant loss of sensitivity.